2015
DOI: 10.1002/app.43260
|View full text |Cite
|
Sign up to set email alerts
|

Design and in vitro investigation of nanocomposite hydrogel based in situ spray dressing for chronic wounds and synthesis of silver nanoparticles using green chemistry

Abstract: An innovative concept of spontaneous film dressing has been designed as sprayed hydrogel dressings (SHD) using a blend of polyvinyl alcohol (PVA) and sodium alginate (SA) as synthetic and natural polymeric components and, were crosslinked with boric acid and calcium chloride, respectively. Silver nanoparticles (AgNPs) are synthesized by green chemistry using Ficus benghalensis extract (FB) and were characterized by SEM and zeta sizer. FTIR spectra show polymeric interaction with AgNP s , while SEM images show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 56 publications
0
29
0
Order By: Relevance
“…Two methods (i.e., the disc diffusion and the CFU) were used to evaluate the antibacterial activity both qualitatively and quantitatively. The disc diffusion method was performed simply by putting the samples onto the bacteria coated agar plates, and then the zone of inhibition was examined after 24 h . CFU method was performed by counting the viable bacterial colonies as described in the literature .…”
Section: Methodsmentioning
confidence: 99%
“…Two methods (i.e., the disc diffusion and the CFU) were used to evaluate the antibacterial activity both qualitatively and quantitatively. The disc diffusion method was performed simply by putting the samples onto the bacteria coated agar plates, and then the zone of inhibition was examined after 24 h . CFU method was performed by counting the viable bacterial colonies as described in the literature .…”
Section: Methodsmentioning
confidence: 99%
“…Poly(vinyl alcohol) (PVA) is a synthetic polymer, which is commonly used in the preparation of biocomposites for various applications, such as wound dressings [2,3] and scaffolds for tissue engineering [4][5][6] due to its biocompatibility and non-toxicity. Due to their exceptional hydrophilicity, with many -OH groups on the side chain, PVA hydrogels are able to swell in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…5. In another study, a novel idea of spontaneous film dressing (SHD) was reported by Kumar [65] . In vitro properties like degradation, microbe penetration assay and water absorption ability were investigated.…”
Section: Hydrogelsmentioning
confidence: 99%